Hierarchy of hybrid materials. Part-II: The place of organics-on-inorganics in it, their composition and applications - Song, Junnan; Vikulina, Anna S.; Parakhonskiy, Bogdan V.; Skirtach, Andre G. (Frontiers in Chemistry, 2023)
Hybrid materials or hybrids incorporating organic and inorganic constituents are emerging as a very potent and promising class of materials due to the diverse but complementary nature of the properties inherent to these different classes of materials. The complementarity leads to a perfect synergy of properties of the desired materials and products as well as to an extensive range of application areas generated by engaging very different research communities. Recently, we have classified hybrid materials describing inorganics-in-organics in Part-I (Saveleva et al., 2019). Here, we extend that work in Part-II describing organics–on-inorganics, i.e., inorganic materials modified by organic moieties. Inorganic colloids/nanoparticles and flat surfaces/matrices comprise of metallic (noble metal, metal oxide, metal-organic framework, magnetic nanoparticles, alloy) and non-metallic (minerals, clays, carbons, and ceramics) materials. Organic additives include chemical molecules(polymers, fluorescence dyes, surfactants) and biomolecules (proteins, carbohydtrates, antibodies and nucleic acids) and higher-level organisms: cells, bacteria, and microorganisms. Similarly to what was described in Part-I, we look at similar and dissimilar properties of organic-inorganic materials summarizing those bringing complementarity and composition. A broad range of applications of these hybrid materials is also presented.